Determination of contract by employer in construction industry - Tay, Lee Yong (2006)
In the construction industry, the standard form of building contract is one of the key methods of ameliorating a potentially fractious relationship to achieve a common end. All standard forms of construction contract contain clauses for determination of contracts. There is a distinction between â€œdeterminationâ€? and â€œterminationâ€?. Briefly, termination of a contract takes place at a point in time in the course of a contract period when a legally binding contract is brought to an end before it has been discharged by performance due to the acts of one or both parties. Under standard form of construction contract, there are several clauses provided for determination of contract by the employer and the determination of contract by contractor. Under both PWD 203A and PAM 1998 standard forms of contract, it has provided several conditions which allow the employer to determinate the contract of the employment. Under both contracts, there are several default by the contractor which will caused the employer to determine their employment, such as suspension of works by contractor; failure to proceed regularly and diligently; failure to remove defective works; assignment or sub-letting without consent; failure to execute works in accordance with the contract and bankruptcy, insolvency, etc of the contractor. Therefore, the employer may determine the contract pursuant the defaults of the contractor. Normally, some of the contractors are unfamiliar with the clauses provided under the contract. Therefore, by investigating the most frequent reasons for determination by employer according to the standard form of contract, it will be able to create awareness among the contractors. So, the contractors can prevent from being determined by the employer.